Impact of Early-Life Brain Injury on Gut Microbiota Composition in Rodents: Systematic Review with Implications for Neurodevelopment - Vanessa da Silva Souza; Raul Manhães-de-Castro; Sabrina da Conceição Pereira; Beatriz Souza de Silveira; Caio Matheus Santos da Silva Calado; Henrique José Cavalcanti Bezerra Gouveia; Jacques-Olivier Coq; Ana Elisa Toscano (Cells, 2025)
Early-life brain injuries are major causes of long-term neurodevelopmental disorders such as cerebral palsy. Emerging evidence suggests these injuries can alter the gut microbiota composition, intestinal integrity, and neuroinflammatory responses. This systematic review evaluated the impact of early-life brain injuries on the gut microbiota in rodent models. A scientific literature search was conducted across Medline/PubMed, Web of Science, Scopus, and Embase. Initially, 7419 records were identified, and 21 eligible studies were included. Eligible studies focused on evaluating the microbiota alterations and related gut–brain axis markers at the neonatal or post-weaning stages. The data extraction and synthesis followed PRISMA guidelines. Most studies reported gut dysbiosis characterized by a decreased abundance of Bacteroidetes, and Lactobacillus. Alterations were associated with an increased gut permeability, reduced tight junction proteins, and elevated pro-inflammatory cytokines. Several studies showed reduced levels of short-chain fatty acids and metabolic pathway disruptions. Brain outcomes included neuroinflammation, white matter injury, altered gene expression, and impaired structural integrity. These results suggest that early-life brain injury induces complex alterations in the gut microbiota and its metabolic products, which may contribute to systemic and neuroinflammatory processes. Understanding these interactions offers insights into the pathophysiology of neurodevelopmental disorders and highlights the gut–brain axis as a potential target for early interventions.